2019
DOI: 10.1002/jlb.2ma1119-174rr
|View full text |Cite
|
Sign up to set email alerts
|

CD226 deficiency on regulatory T cells aggravates renal fibrosis via up-regulation of Th2 cytokines through miR-340

Abstract: In this study, we observed that deletion of CD226 on regulatory T cells (Tregs) precedes renal fibrosis in a mouse unilateral ureteral obstruction (UUO) model. First, we generated Treg‐specific CD226 gene knockout mice (CD226fl/fl Foxp3YFP‐Cre). Next, CD226fl/fl Foxp3YFP‐Cre mice and Foxp3YFP‐Cre control mice were subjected to UUO surgery. Pathologic analysis and Sirius red and Masson's trichrome staining showed that the kidneys of CD226fl/fl Foxp3YFP‐Cre mice following UUO showed much more severe interstitial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 47 publications
(86 reference statements)
0
12
0
Order By: Relevance
“…Several studies have demonstrated that a deficiency or blockade of DNAM-1 increases the numbers of Foxp3 + cells and enhances Treg cell function in mouse models of acute graft-versus-host disease (GVHD), unilateral ureteral obstruction, and allogeneic skin transplantation (18)(19)(20), suggesting that DNAM-1 suppresses, rather than enhances, Treg cell function. In sharp contrast, TIGIT promotes the production of anti-inflammatory cytokines, such as IL-10 and fibrinogen-like protein 2 (Fgl2), by Treg cells, thus suppressing Th1 and Th17 reactions (21) and suggesting that TIGIT is involved in the immune-suppressive function of Treg…”
mentioning
confidence: 99%
“…Several studies have demonstrated that a deficiency or blockade of DNAM-1 increases the numbers of Foxp3 + cells and enhances Treg cell function in mouse models of acute graft-versus-host disease (GVHD), unilateral ureteral obstruction, and allogeneic skin transplantation (18)(19)(20), suggesting that DNAM-1 suppresses, rather than enhances, Treg cell function. In sharp contrast, TIGIT promotes the production of anti-inflammatory cytokines, such as IL-10 and fibrinogen-like protein 2 (Fgl2), by Treg cells, thus suppressing Th1 and Th17 reactions (21) and suggesting that TIGIT is involved in the immune-suppressive function of Treg…”
mentioning
confidence: 99%
“…Tek cre mice were purchased from the Jackson Laboratory (Bar Harbor, ME, USA). CD226 fl/fl mice on a C57BL/6 background were generated by Cyagen Biosciences (Suzhou, China) 22 . Homozygous CD226 + (CD226 fl/fl ) mice were crossed with Tek cre mice to get CD226 fl/wt Tek cre mice that were then self‐crossed to obtain CD226 fl/fl Tek cre (CD226 conditional knockout [CKO]) and CD226 wt/wt Tek cre (wild‐type, WT) mice, which were identified by genotyping and immunofluorescence staining (as follow).…”
Section: Methodsmentioning
confidence: 99%
“…CD226 fl/fl mice on a C57BL/6 background were generated by Cyagen Biosciences (Suzhou, China). 22 Homozygous CD226 + (CD226 fl/fl ) mice were crossed with Tek cre mice to get CD226 fl/wt Tek cre mice that were then self-crossed to obtain CD226 fl/fl Tek cre (CD226 conditional knockout [CKO]) and CD226 wt/wt Tek cre (wild-type, WT) mice, which were identified by genotyping and immunofluorescence staining (as follow). For HS modeling, male C57BL/6 mice, aged 8-12 weeks and weighing 20-25 g, were randomly divided into HS and sham groups.…”
Section: Introductionmentioning
confidence: 99%
“…The Treg-macrophage inhibitory interaction was transforming growth factor-β (TGF-β)-dependent (Mahajan et al, 2006 ). Besides that, CD226 deficiency on Tregs exacerbated renal fibrosis in the UUO model by upregulating Th2-related cytokines like IL-4 (Mu et al, 2020 ). Recently, a single-cell RNA sequencing study showed that tissue-resident IL-33R + and IL-2Ra + Tregs markedly increased following injury in the two mouse models of either kidney repair or fibrosis.…”
Section: Regulatory T Cellsmentioning
confidence: 99%